2008
DOI: 10.1177/1362361307089520
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of biological motion in children with autistic spectrum disorders

Abstract: It is widely accepted that autistic children experience difficulties in processing and recognizing emotions. Most relevant studies have explored the perception of faces. However, context and bodily gestures are also sources from which we derive emotional meanings. We tested 23 autistic children and 23 typically developing control children on their ability to recognize point-light displays of a person's actions, subjective states an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
89
2
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(105 citation statements)
references
References 23 publications
11
89
2
3
Order By: Relevance
“…Impairment of this integration has indeed been reported in ASD (Spencer et al 2000;Milne et al 2002;Pellicano et al 2005;Milne et al 2006;Tsermentseli et al 2008;Atkinson 2009). In addition, individuals with ASD show deficits in the discrimination of biological motion (Blake et al 2003;Parron et al 2008;Klin et al 2009;Annaz et al 2010) and in the recognition of emotions from body movements (Hubert et al 2007;Atkinson 2009), both often tested with "point-light displays" (PLDs) of actions (Johansson 1973). The ability to extract social information from PLDs is an indication that complex social cognition can be performed on the basis of basic perceptual input (Adolphs, 2003), and thus, reduced sensitivity to PLDs of emotions has often been taken as evidence for compromised social functioning in ASD.…”
mentioning
confidence: 99%
“…Impairment of this integration has indeed been reported in ASD (Spencer et al 2000;Milne et al 2002;Pellicano et al 2005;Milne et al 2006;Tsermentseli et al 2008;Atkinson 2009). In addition, individuals with ASD show deficits in the discrimination of biological motion (Blake et al 2003;Parron et al 2008;Klin et al 2009;Annaz et al 2010) and in the recognition of emotions from body movements (Hubert et al 2007;Atkinson 2009), both often tested with "point-light displays" (PLDs) of actions (Johansson 1973). The ability to extract social information from PLDs is an indication that complex social cognition can be performed on the basis of basic perceptual input (Adolphs, 2003), and thus, reduced sensitivity to PLDs of emotions has often been taken as evidence for compromised social functioning in ASD.…”
mentioning
confidence: 99%
“…These studies have suggested that individuals with autism are unaffected in the perceptual processing of form-from-motion, but may exhibit impairments in higher order judgments such as emotion processing (Atkinson, 2009;Hubert et al, 2007;Moore, Hobson, & Lee, 1997;Parron, Da, Santos, Moore, Monfardini, & Deruelle, 2008).…”
Section: The Biological Motion Preference Hypothesismentioning
confidence: 99%
“…In addition to gender, the 24 children in the second comparison group were individually matched to the children in the deaf group for chronological age (CA-matched, aged from 6 years 4 months to 17 years, mean chronological age = 12 years 5 months, SD = 2 years 4 months). This matching procedure has been adopted in a number of published studies using PLDs (e.g., Parron et al, 2008;Hubert et al, 2007) and allows interpretation of results in terms of developmental delay and/or developmental deviance. By comparing with a CA-match group, any individual differences found in deaf children would suggest developmental delay.…”
Section: Participantsmentioning
confidence: 99%
“…This work has built on earlier findings showing deficits in ToM and emotional face-processing (e.g., Celani, Battacchi & Arcidiacono, 1999). The study, carried out by Parron et al (2008) investigated action and emotion interpretation using point light displays (PLD) in children with ASD. These findings revealed a dissociation with impaired performance relative to age and intelligence matched controls on PLDs with emotional value, but no impairment relative to controls, on PLDs depicting simple personal actions, subjective states and objects.…”
mentioning
confidence: 99%
See 1 more Smart Citation